Soaking Feet in Warm Water for Hypertension Patient: Case Study - Sri Rezeki, Nandini; Puspita, Tantri (Nursing Case Insight Journal, 2023)
Hypertension or commonly called high blood pressure is an increase in systolic blood pressure above the normal limit, which is more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Pain is a symptom that arises due to high blood pressure. One of the non-pharmacological therapies that can be used to reduce pain directly and indirectly reduce blood pressure is hydrotherapy. This case study aims to determine the effectiveness of foot soaks using warm water to reduce blood pressure in hypertensive patients. The method used is a descriptive case study by taking anamnesis, observation, physical examination, and medical records. The participant in this study was diagnosed with hypertension sufferers and the blood pressure was measured by a sphygmomanometer. It was found that the client's blood pressure can be overcome by soaking the feet in warm water to lower blood pressure. Provision of hydrotherapy was carried out for 4 days of administration in 1 day 1 time with a duration of 15 minutes effect to lower blood pressure from 170/100 mmHg drops to 140/90 mmHg. Hydrotherapy can be a non-pharmacology intervention from a nurse.